Examination of the Factor Structure of Psychopathology in a Mozambican Sample. (May 2023) - Giusto, Ali; Romer, Adrienne; Lovero, Kathryn; dos Santos, Palmira Fortunado; Greene, Claire; Gouveia, Lidia; Suleman, Antonio; Feliciano, Paulino; Oquendo, Maria A.; Mootz, Jennifer; Wainberg, Milton L.
Factor-analytic studies are needed in global samples to advance understanding of psychopathology. Here, we examined the structure of psychopathology and a general psychopathology (p) factor using data from a cross-sectional study of 971 adults (63% women) from Maputo City, Mozambique. We used confirmatory factor analyses of symptoms from 15 psychiatric disorders to test common models of the structure of psychopathology. Models that included Internalizing, Substance Use, and Thought Disorder factors as well as a general p factor fit the data well. Measurement invariance testing revealed that factor loadings on p differed by gender. Higher levels of p, Internalizing, and Thought Disorder factors were associated with greater suicide risk, psychiatric comorbidity, chronic medical illnesses, and poorer functioning. A general p factor and Internalizing, Substance Use Disorder, and Thought Disorder factors were identifiable in this Mozambican sample. Understanding psychopathology dimensions is a step toward building more scalable mental health service approaches globally.